Selection of online shopping with the electree method - Panjaitan, Dedy Juliandri; Aprilia, Rima (ZERO: Jurnal Sains, Matematika dan Terapan, 2020)
E-Commerce stands for Electronic Commerce which means a marketing system by means of electronic media. E-Commerce is defined as the process of buying and selling of products, services and information that is done electronically using a computer network. One form of e-commerce is online shopping. The purpose of this study is to determine the best online shopping based on predetermined criteria. The criteria used in E-Commerce are the price of goods, completeness of goods, shipping costs, quality of goods, and length of delivery time. The Electre method is a multi-criteria decision-making method based on the concept of outranking using pairwise comparisons of alternatives based on each appropriate criterion. Based on the analysis using the Electric method, it is recommended that the best online shopping is TOKOPEDIA which dominates other alternatives.